2020
DOI: 10.1111/bjdp.12344
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic awareness of age‐related losses predict concurrent and subsequent changes in daily inductive reasoning performance

Abstract: To address gaps in previous research, we examined daily within-person associations between awareness of age-related change (AARC) and cognitive performance in older adults. One hundred twelve adults aged 60-90 participated in an online daily diary study for nine consecutive days. On Day 1, they reported demographic information. On Days 2-9, they reported daily AARC, subjective age, and stressors and completed three tasks that gauged memory (word recall), perceptual speed (number comparison), and reasoning (let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 60 publications
4
26
0
Order By: Relevance
“…This finding was consistent across all age subgroups but strongest in advanced old age; supporting the greater accuracy of older individuals in reporting cognitive difficulties (Jessen et al, 2014). A recent study examining daily within-person variability in AARC and cognitive performance showed that AARC losses predict within-person decreases in inductive reasoning on the same day and decreases from day 1 to the next (Zhu and Neupert, 2020). Despite the methodological differences between this study and ours, both found that among several cognitive domains AARC is most strongly associated with reasoning.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This finding was consistent across all age subgroups but strongest in advanced old age; supporting the greater accuracy of older individuals in reporting cognitive difficulties (Jessen et al, 2014). A recent study examining daily within-person variability in AARC and cognitive performance showed that AARC losses predict within-person decreases in inductive reasoning on the same day and decreases from day 1 to the next (Zhu and Neupert, 2020). Despite the methodological differences between this study and ours, both found that among several cognitive domains AARC is most strongly associated with reasoning.…”
Section: Discussionsupporting
confidence: 56%
“…Eighth, the cognitive tests were completed on a separate day (within 2 months) to that on which participants answered the AARC questionnaires. This is a limitation as levels of perceived cognitive gains and losses can vary on a daily basis (Zhu and Neupert, 2020). However, cognitive functioning among individuals without dementia is generally stable over 2 months (e.g.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Daily fluctuation in AARC is related to fluctuation in other variables such as levels of positive and negative affect (Neupert and Bellingtier, 2017) and control beliefs (Zhang and Neupert, 2020). As daily fluctuation in AARC influences daily cognitive performance (O'Brien et al, 2020; Zhu and Neupert, 2020), the fluctuating nature of AARC gains and losses may limit the predictive accuracy of the AARC questionnaire. It would, therefore, be important in future research to control for variables (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, by exploring, for the first time, changes in cognitive functioning as predictors of AARC-gains and AARC-losses, this study made it possible to extent previous cross-sectional and micro-longitudinal evidence on the associations of AARC-gains and AARC-losses with cognitive functioning (Sabatini, Ukoumunne, Ballard, Collins, Anstey, et al, 2021; Zhu & Neupert, 2021). We confirmed that the association between poorer cognition and more AARC-losses is consistently small also at the longitudinal level.…”
Section: Discussionmentioning
confidence: 99%